2014
DOI: 10.3390/rs61110931
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Vegetation over a Residual Megafan Landform in the Amazonian Lowland Based on Optical and SAR Imagery

Abstract: Abstract:The origin of large areas dominated by pristine open vegetation that is in sharp contrast with surrounding dense forest within the Amazonian lowland has generally been related to past arid climates, but this is still an issue open for debate. In this paper, we characterize a large open vegetation patch over a residual megafan located in the northern Amazonia. The main goal was to investigate the relationship between this paleolandform and vegetation classes mapped based on the integration of optical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Furthermore, objects enable the consideration of semantic or spatial contextual relationships, which helps to cope with heterogeneous feature such as TFV [6,11]. Several segmentation techniques, which group pixels into meaningful or perceptual regions (objects) for the extraction of TFV, can be found in the literature, including multiresolution segmentation [24,41], Mallat's discrete wavelet transform [42], Markov Random Fields [14,43], and clustering approaches [10,11]. The combination of segmentation techniques with SAR time-series data can be used to discover multi-temporal characteristics and patterns, allowing for the extraction of useful information from enormous and complex data sets [44] and empowering the derivation of time series features with the advantages of an object-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, objects enable the consideration of semantic or spatial contextual relationships, which helps to cope with heterogeneous feature such as TFV [6,11]. Several segmentation techniques, which group pixels into meaningful or perceptual regions (objects) for the extraction of TFV, can be found in the literature, including multiresolution segmentation [24,41], Mallat's discrete wavelet transform [42], Markov Random Fields [14,43], and clustering approaches [10,11]. The combination of segmentation techniques with SAR time-series data can be used to discover multi-temporal characteristics and patterns, allowing for the extraction of useful information from enormous and complex data sets [44] and empowering the derivation of time series features with the advantages of an object-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…They used ten sets of ALOS/PALSAR data over four years to examine temporal variations and found that the functional relation of aboveground biomass and backscatter were dependent on precipitation. Moreover, Cremon et al [39] employed a decision tree classifier to map forest and open vegetation over a residual megafan located in a wetland area in the Amazonian lowland based on the integration of optical Landsat TM and ALOS/PALSAR SAR data, and indicated that the vegetation distribution highlights a morphology attributed to a previously developed Quaternary megafan. At a global level, Shimada et al [182] generated forest/non-forest maps based on annual mosaics derived from ALOS/PALSAR HH and HV polarization data at a 25-m spatial resolution for the years 2007 to 2010.…”
Section: Hydrosphere: Inundation/floodingmentioning
confidence: 99%
“…For example, L-band data have been applied and investigated for the following topics: the detection and mapping of flooded vegetation and inundated areas; the retrieval of aboveground biomass; and the estimation of soil moisture. Vegetation-related research is the most-often published subject; a lot of work has been done in the field of forestry [38][39][40][41] and wetland research [42][43][44][45][46][47][48]. In the context of coastal zone-related studies, the potential of L-band SAR data has been demonstrated for the mapping and monitoring of flooded vegetation [25,49,50], wetland extents and wetland inundation [26,[51][52][53][54][55][56] and for the assessment of mangrove forests [47,57,58].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the combined use of different sensors for vegetation monitoring, the studies can be divided into two types: one uses the heterogeneous data from different sensors such as LiDAR with optical sensors [8][9][10][11], synthetic aperture radar (SAR) with optical sensors [12,13] and high geometrical resolution images with hyper/multi spectral images [14]; the other category is through the synthetic use of similar sensors from different platforms, such as TLS with ALS [15], airborne with space-borne and so on.…”
Section: Introductionmentioning
confidence: 99%